Korelasi Ketersediaan APD, Peraturan, dan Pengawasan dengan Kepatuhan Penggunaan Alat Pelindung Diri (APD) pada Petugas Bagian Laundry, Dapur, dan Kebersihan RSI Siti Rahmah - Novia Zulfa Hanum; Rahmanita Yusman; Yori Rahmadianti (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
To improve the competitiveness and productivity of hospitals, it is necessary to apply the OSH culture. One indicator is the use of PPE. The purpose of research is to to know the relationship of availability of PPE, regulations, and supervision of use PPE in laundry, kitchen, and cleaning services in Siti Rahmah Islamic Hospital. Laundry, kitchen, and cleaning services have a high risk for working accidents and occupational diseases. The research method is quantitative analysis method with cross sectional design at Siti Rahmah Islamic Hospital in January-December 2022. Population in this research totally 43 persons. all populations are sampled in this study The analysis used in this research is univariate and bivariate. The results showed that availability of PPE (0,041), regulations (0,000), and supervision (0,000) significantly correlate with the use of PPE. It is recommended for officers to get used to using PPE when doing work. Siti Rahmah Islamic Hospital is advised to provide socialization or training regarding the use of PPE. In addition, it is hoped that Siti Rahmah Islamic Hospital will be able to ensure the availability of PPE and supervision of the use of PPE.